MENINGKATKAN PENGETAHUAN SISWA TENTANG SIRAH NABI PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM - Rahmah, St. R; Kaliky, Muhamad Faisal (Uniqbu Journal of Social Sciences, 2023)
The purpose of this study is to explain the History of Islamic Culture in Madrasas in order to increase students’ understanding of the Prophet’s sirah. While the research method used in this paper is qualitative. Where the researcher will describe the data in the form of sentences. The researchers employed descriptive research methods. Whereas the descriptive approach describes only the phenoma, symptoms, events, and events that occur. The findings of this paper indicate that; The Islamic Cultural History subject teacher at Madrasah Tsanawiyah Negeri 2 Bantaeng begins by introducing the class with the goal of knowing students’ readiness in learning, neatness in dressing, and time discipline. After that, proceed with prayer and tadarus Al-Qur’an in class for 10 to 15 minutes before learning begins. There are also programs that continuously implement the dhuha prayer in each class, the dhuhur prayer in congregation, and the reading of Yasin’s letter every Friday. Before beginning the teaching and learning process, the teacher of the Islamic Cultural History subject at Madrasah Tsanawiyah Negeri Bantaeng compiled and prepared learning tools in the form of learning implementation plans, assessments and evaluations based on teacher books and student books, as well as curriculum demands, to measure students’ abilities and success, both during the learning process and over the course of one semester.